An introduction to Catholic social thought - Hornsby-Smith, Michael P. 1932- (Cambridge [u.a.] Cambridge University Press, 2006)
Michael Hornsby-Smith offers an overview of Catholic social thought particularly in recent decades. While drawing on official teaching such as papal encyclicals and the pastoral letters of bishops' conferences, he takes seriously the need for dialogue with secular thought. The book is organized in four stages. Part I outlines the variety of domestic and international injustices and seeks to offer a social analysis of the causes of these injustices. Part II offers a theological reflection on the characteristics of the kingdom of God which Christians are urged to seek. Part III reviews Catholic social thought in six main areas: human rights, the family and bioethical issues, economic life, social exclusion, authentic development, and war and peace. Part IV completes the cycle with a consideration of appropriate social action responses to the injustices which the author has identified and analysed.
Includes bibliographical references (p. 346 - 363) and index
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Archivierung prüfen
Keywords: Christian Sociology -- Catholic Church; Church and social problems -- Catholic Church; Church and social problems -- Catholic Church; Christian Sociology -- Catholic Church; Lehrbuch